CHRONICLES OF HEALING: UNVEILING THE SECRETS OF ABRASION AND LACERATION DATING IN FORENSIC PATHOLOGY - CHOYAL, MAHAVEER; BANSOD, PRIYANKA; VYAS, P. C.; KOODI, GURUSHARAN (International Journal of Current Pharmaceutical Research, 2024)
Objective: In the field of forensic pathology, understanding the timeline of injury occurrence is of paramount importance. This study, titled "Chronicles of Healing: Unveiling the Secrets of Abrasion and Laceration Dating in Forensic Pathology," conducted a postmortem investigation to assess wound dating by gross and histopathological examination of blunt injuries. Methods: A total of 195 case samples from 119 cases were scrutinized to establish the timing of various gross changes and microscopic alterations that transpire following blunt trauma. The study encompassed abrasions, contusions, and lacerations occurring within a time frame ranging from 0 h to a maximum of 45 d. Results: The findings revealed that the gross changes in abrasions closely correlated with the corresponding microscopic changes, while contusions exhibited a similar correlation, except for a variation in the appearance of bluish color. In lacerations, the correlation was primarily evident during the early stages of injury. Conclusion: Importantly, the study emphasized the substantial impact of comorbid conditions on the healing process, highlighting the need for cautious evaluation in such cases. The study concludes that naked eye examination alone is insufficient for precise injury dating, underscoring the importance of histopathological examination to ensure accurate conclusions regarding injury age.